Dose Delivered to the Lumbosacral Plexus From High-Dose-Rate Brachytherapy for Cervical Cancer. Issue 5 (1st June 2015) - Rash, Dominique; Durbin-Johnson, Blythe; Lim, Jihoon; Dieterich, Sonja; Huddleston, Adam; Yi, Sun; Mayadev, Jyoti
Abstract : Objective: To calculate dose delivered to the lumbosacral plexus (LSP) with cervical brachytherapy using 3-dimensional imaging, and to compare this with the position of the tandem in the pelvis using bony landmarks. We also report long-term LSP toxicity outcomes. Methods and Materials: Treatment planning images from 55 patients treated with tandem and ring brachytherapy from October 2009 through November 2012 were reviewed. The LSP was contoured on planning computed tomographic scans to calculate dose received. Lumbosacral plexus dose was studied as a function of tandem distance from the sacrum and pubic symphysis (STratio) measured on digitally reconstructed radiographs. Patient and implant characteristics were included as covariates on LSP dose. Clinical follow up on LSP toxicity was recorded. Results: Patients were prescribed 550 to 700 cGy using computed tomography–based imaged-guided brachytherapy for 4 to 5 fractions. The maximum dose to 2 cc (D2cc) of LSP ranged from 44 to 287 cGy per implant. The median D2cc was 118 cGy, corresponding to 18% of prescription dose. Patients with an STratio less than 0.33 (closer to the sacrum) and at least 0.33 had median LSP doses of 138 and 98 cGy, respectively. Lumbosacral plexus dose did not change significantly with body mass index, uterus position, or tumor stage. Two patients reported symptoms of peripheral neuropathy, with a median follow-up of 14.7 months. Conclusions: The mean D2cc per fraction to the LSP is roughly 20% of the prescribed high dose-rate and varies with the position of the tandem from the sacrum. The dose threshold for radiation-induced neuropathy of the LSP remains undefined.